Antifungal use in children with acute leukaemia: state of current evidence and directions for future research. (18th March 2022) - Yeoh, Daniel K.; Haeusler, Gabrielle M.; McMullan, Brendan J.; Butters, Coen; Bryant, Penelope A.; Clark, Julia E.; Cooper, Celia M.; Gwee, Amanda; Kotecha, Rishi S.; Lai, Tony; Slavin, Monica A.; Thursky, Karin A.; et al.
Abstract: Invasive fungal disease (IFD) remains a common and serious complication in children treated for leukaemia. Antifungal prescription in children with leukaemia presents unique challenges, particularly due to variation in IFD risk between and within leukaemia treatment protocols, drug toxicities and interactions between antifungals and chemotherapeutic agents. With recent advances in the understanding of IFD epidemiology and large clinical trials in adults assessing antifungals for IFD treatment and prophylaxis, together with paediatric clinical and pharmacokinetic studies, there is a growing body of data to inform optimal antifungal use in children. A panel of infectious diseases and haematology-oncology clinicians with expertise in IFD management compiled a list of 10 key clinical questions following development of the 2021 Australia and New Zealand Mycology Antifungal Consensus Guidelines. A focused literature review was conducted to explore available evidence and identify gaps in knowledge to direct future research. With the changing epidemiology of IFD globally, the ongoing evolution of paediatric leukaemia treatment and the increasing availability of novel antifungal agents, advocacy for paediatric clinical studies will remain vital to optimize IFD prevention and treatment in children with leukaemia.